Kinase Domain Is a Dynamic Hub for Driving LRRK2 Allostery - Taylor, Susan S.; Kaila-Sharma, Pallavi; Weng, Jui-Hung; Aoto, Phillip; Schmidt, Sven H.; Knapp, Stefan; Mathea, Sebastian; Herberg, Friedrich W. (Frontiers in Molecular Neuroscience, 2020)
Protein kinases and GTPases are the two major molecular switches that regulate much of biology, and both of these domains are embedded within the large multi-domain Leucine-Rich Repeat Kinase 2 (LRRK2). Mutations in LRRK2 are the most common cause of familial Parkinson’s Disease (PD) and are also implicated in Crohn’s disease (Hui et al., 2018). The recent Cryo Electron Microscopy (Cryo-EM) structure of the four C-terminal domains (RCKW) of LRRK2 includes both of the catalytic domains (Deniston et al., 2020). Although the important allosteric N-terminal domains are missing in the Cryo-EM structure this structure allows us to not only explore the conserved features of the kinase domain, which is trapped in an inactive and open conformation, but also to observe the direct allosteric cross talk between the two domains. To define the unique features of the kinase domain and to better understand the dynamic switch mechanism that allows LRRK2 to toggle between its inactive and active conformations, we have compared the LRRK2 kinase domain to Src, BRaf, and PKA. We also compare and contrast the two canonical glycine-rich loop motifs in LRRK2 that anchor the nucleotide: the G-Loop in protein kinases that anchors ATP and the P-Loop in GTPases that anchors GTP. The GTPase domain of LRRK2 belongs to the Roco protein family and plays an important role as an allosteric effector domain (Bosgraaf et al., 2003, Marin et al., 2008). The RCKW structure also provides a template for the cross-talk between the kinase and GTPase domains and brings new mechanistic insights into the physiological function of LRRK2 and how the kinase domain, along with key phosphorylation sites, can serve as an allosteric hub for mediating conformational changes.